(untitled) (Jurnal Proaksi, 2019)
The purpose of this research is to find out and learn how much influence the sales accounting information system, the cash receipt accounting information system on the effectiveness of controlling accounts receivable. The population in this study is limited to PT Tera Data Indonesia’s employees. The sampling technique was 30 respondents. Data collection techniques use primary and secondary data with the help of SPSS version 20. For windows. From the test results it can be concluded that the credit sales accounting information system, the cash receipt accounting information system has an effect on the effectiveness of the accounts receivable control. Keyword : Credit Sales Accounting Information Systems, Accounting Information Systems Cash Receipts, Accountability Control Effectiveness.